Human Resource Planning on Organization Performance in Cooperatives Sector - Aryal, Narayan Prasad; Singh, Gobind Kumar (Journal of Development Review, 2023)
The study investigates the empirical examination of human resource planning in the cooperative sector. It aims to assess the impact of forecasting manpower demand and strategic action on the overall performance of these organisations. This paper aims to provide a comprehensive analysis of the intricate relationship between human resource planning and organisational performance. The selection of firms was conducted using stratified sampling techniques within the cooperative sector. The exploratory research design was selected as the primary research paradigm to uncover and understand reality. In this quantitative study, information came from a sample of 54 cooperative employees, specifically in the areas of Kalimati, Balkhu, and Teku. A meticulously developed structured questionnaire was employed, and the resulting data were subjected to analysis utilising SPSS version 20. Data collection has been conducted using convenience sampling. The results of the study suggest a noteworthy correlation between human resource planning and organisational effectiveness. Based on the findings, it is recommended that the cooperative sector and its human resource managers should consistently conduct manpower audits and planning. This will allow them to proactively assess the demand and supply situation in the labour market before proceeding with employee recruitment.